Contamination of liposomal bupivacaine during multi-dose usage in a clinical setting evaluated by culture and PCR - Melvin, Rachel L.; Wu, Jing; Bennett, Brad S.; Lawhon, Sara D.; Savarino, Amy; Rogovskyy, Artem S.; Thieman Mankin, Kelley M. (Frontiers in Veterinary Science, 2024)
IntroductionLiposomal bupivacaine, a long-acting local anesthetic, is sold in single-dose vials at a cost of approximately $200/20 mL vial. As many veterinary patients are not dosed an entire vial, the vials have been used for multiple doses at our institution to provide cost savings. Multiple punctures of a vial can lead to increased opportunity for contamination of the contents. This study aims to describe our institutional procedure for multi-dose use of single-dose liposomal bupivacaine vials and to evaluate clinically utilized liposomal bupivacaine for bacterial and fungal contamination using molecular and bacteriological methods.MethodsThe first (Control) and last (Sample B) 0.5 mL from each vial were collected and submitted for bacterial and fungal PCR, anaerobic and aerobic bacterial culture, and opportunistic fungal culture.ResultsAll 40 bacterial cultures yielded no growth; Bacterial or fungal DNA was identified in 19 samples (50%). Of the 19 samples in which bacterial or fungal DNA was identified, 10 (52.6%) were from Control, and 9 (47.4%) were from Sample B. PCR does not appear to be useful in detecting bacterial or fungal contamination from liposomal bupivacaine.DiscussionResults support the aseptic handling protocol described in this article is successful in preventing detectable bacterial and fungal contamination of liposomal bupivacaine vials for up to 7 individual punctures and vials open for up to 5 days.